Analytic philosophy: the desire for the truth and the temptation to doubt (Diametros, 2010)
Review of the book: Peter Prechtl, Leksykon pojęć filozofii analitycznej, przeł. Józef Bremer, Wydawnictwo WAM, Kraków 2009